EXPECTATIONS FROM CURRICULUM OF RELIGIOUS EDUCATION IN CONTEXT OF COMMUNICATION WITH DIFFERENT RELIGIOUS GROUPS (IN CASE OF TURKS WHO LIVE IN WESTERN COUNTRIES) - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2015)
Globalization is accepted generally as main feature of our world in the present. Important characteristics of globalization are pluralism and multi-culturalism. Fact of emigration plays important role in emerging of these characteristics by transformation of societies to pluralistic structure. Depending on changing of social structure these characteristics affects educational systems and politics towards regulation of curriculum and methods through acceptance of differences especially in destination countries for emigration. Because it's seen as important to accept differences and knowing of them for living together peacefully rather differences. Tendency of pluralism and multi-culturalism in educational system also important for religious education. Because necessity of getting mutual information about different religious groups is emphasized as important point that should be considered in process of preparing of curriculum for religious education. From these points, we intented to understand needs and expectations of Turks from religious education who live in Western countries with different religious groups in context of knowledge and communication with different religious groups. We surveyed on 250 Turks from different Western countries such as Britain, Germany, France and even USA asking their needs and expectations from religious education considering their sources for religious knowledge, their tendency to communicate with different religious groups. We want to share results of our survey to discuss on curriculum of religious education for them.
Keywords: Religion; Religious Education; Religious Knowledge; Curriculum; Religious Pluralism